A2 4 Mass Confusion: Investigating Weight Classification in Mario Kart Wii - Lewis, Dan; Scivener, Callum; Dyer, Thomas (Physics Special Topics, 2024)
In this paper, we look to investigate if the current weight class system in Mario Kart Wii is feasible. We find that although separating characters based on mass is logical, the current iteration does not align with the physical forces experienced. Therefore, we have suggested the movement of Koopa Troopa and Waluigi to the Heavy and Medium weight classes respectively, as well as the introduction of a Super Heavy class for Dry Bowser and Bowser Jr.